The Effect Of Teller Service Excellence On Customer Satisfaction at PT. Bank Negara Indonesia (Persero), Tbk. Bondowoso Branch Office - Mohammad Fathul Muin; Maheni Ika Sari; Ira Puspita Dewi S (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Banks as one of the financial institutions engaged in services, must be able to provide the best service (service excellence) in order to win the increasingly competitive competition, thereby providing satisfaction to customers. PT. Bank Negara Indonesia (Persero), Tbk. KCP Bondowoso is a bank that competes with other banks including BRI, Bank Mandiri, BSI, and others, PT. Bank Negara Indonesia (Persero), Tbk. KCP Bondowoso competes to increase customer satisfaction, so that customer loyalty is formed. PT. Bank Negara Indonesia, Tbk has proven its consistency in increasing customer satisfaction in conducting banking transactions. The purpose of this study is to determine and analyze whether ability, attitude, appearance, attention, action and accountability have a significant effect on customer satisfaction at PT. Bank Negara Indonesia (Persero), Tbk. KCP Bondowoso. This type of research is causality research. The population in this study are all customers of PT. Bank Negara Indonesia (Persero), Tbk. Bondowoso KCP using teller services in November 2021 totaled 2,760 people. The sample used was 97 respondents using a purposive sampling technique. The analysis tool uses multiple linear regression. The results of the study prove that ability, attitude, appearance, attention, action and accountability have a significant effect on customer satisfaction at PT. Bank Negara Indonesia (Persero), Tbk. KCP Bondowoso.